Under-reporting of energy and nutrient intake is a persistent issue in the Malaysian Adult Nutrition Surveys - Zainuddin, Ahmad Ali; Md Nor, Norazmir; Md Yusof, Safiah; Ibrahim, Adriana Irawati Nur; Aris, Tahir; Foo, Leng Huat (Nutrition Society of Malaysia, 2019)
Introduction: Under-reporting of energy intake is a common cause of bias in nutritional studies. This study was aimed at examining the extent of underreporting of energy intake and its related characteristics among respondents in the Malaysian Adult Nutrition Survey (MANS) 2003 and MANS 2014. Methods: The present study analysed energy intakes of 9,624 adults aged 18-59 years from the MANS in year 2014 (2,890 respondents) and 2003 (6,734 respondents) using a single 24-hour diet recall. Basal metabolic rates (BMR) were calculated from the age- and gender-specific equations of Schofield. Under-reporting was defined as an energy intake:BMR ratio of <1.2 as proposed by Goldberg. Results: Under-reporting was found to have increased significantly from 53% in 2003 to 61% in 2014. In both surveys, under-reporting increased with higher body mass index (BMI) and older age groups. It was higher among women than men, lowest among those with primary schooling or below, and those living in Peninsular Malaysia. It was higher among rural respondents in 2014 but higher among urban respondents in 2003. The intake of energy and micronutrients increased when under-reporters were excluded. Conclusion: Under-reporting was prevalent in both the nationwide MANS, and is associated with BMI, age, gender, education level, location strata, zone. It is important to take this factor into account when assessing dietary intake in population-based studies. © 2019, Malaysian Journal of Nutrition.